1982
DOI: 10.1111/j.1467-8470.1982.tb00391.x
|View full text |Cite
|
Sign up to set email alerts
|

The Tasman connection: aspects of Australian‐New Zealand relations

Abstract: Although geographers frequently claim an interest in the study of spatial interactions there are few wide ranging studies of relationships between specific areas or countries. Australian and New Zealand geographers have treated their countries' inter‐relationships as marginal asides rather than as serious research themes. From a wide possible agenda the following aspects of trans‐Tasman relationships are examined: the interchange of plants and animals. New Zealand's nineteenth century peripheral relationship t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Vaggioli ([1896] 2000:112), for example, showed that of the 12,447 Europeans in New Zealand in 1844, 3464 or 27.8% lived in Auckland, the Bay of Islands, or Hokianga 12 and stated that “colonists who settled the upper half of the North Island were mostly migrants from Australia” ([1896] 2000:112). In addition, McCaskill (1982:6–7) claimed that “in socio-economic terms, much of the European community in northern New Zealand in the 1830s was a ‘drop-out’ extension of Sydney society with escaped convicts, former convicts, debtors, traders and land speculators enjoying an early kind of ‘enterprise zone’ free of oversight and the law.” In a detailed paper on migration between New Zealand and Australia, Carmichael (1993:516) claimed that many of the estimated 2000 first settlers to New Zealand had come from Australia: “By 1854, the European population totalled 32,500 … 12,000 in Auckland, a garrison town with probably over half its European population … having come from Australia.” In addition, he quoted William Fox (a former premier of New Zealand) who described Auckland in the early 1850s as “a mere section of the town of Sydney transplanted” (Carmichael, 1993:516; Sinclair, 1959:98). In addition, Arnold (1994:120) suggested that “many settlers had a period of Australian experience behind them, and an intricate network of interrelationships gave a significant Australasian dimension to colonial New Zealand.”…”
Section: [Aʊ] [εʊ] and The Settlersmentioning
confidence: 99%
“…Vaggioli ([1896] 2000:112), for example, showed that of the 12,447 Europeans in New Zealand in 1844, 3464 or 27.8% lived in Auckland, the Bay of Islands, or Hokianga 12 and stated that “colonists who settled the upper half of the North Island were mostly migrants from Australia” ([1896] 2000:112). In addition, McCaskill (1982:6–7) claimed that “in socio-economic terms, much of the European community in northern New Zealand in the 1830s was a ‘drop-out’ extension of Sydney society with escaped convicts, former convicts, debtors, traders and land speculators enjoying an early kind of ‘enterprise zone’ free of oversight and the law.” In a detailed paper on migration between New Zealand and Australia, Carmichael (1993:516) claimed that many of the estimated 2000 first settlers to New Zealand had come from Australia: “By 1854, the European population totalled 32,500 … 12,000 in Auckland, a garrison town with probably over half its European population … having come from Australia.” In addition, he quoted William Fox (a former premier of New Zealand) who described Auckland in the early 1850s as “a mere section of the town of Sydney transplanted” (Carmichael, 1993:516; Sinclair, 1959:98). In addition, Arnold (1994:120) suggested that “many settlers had a period of Australian experience behind them, and an intricate network of interrelationships gave a significant Australasian dimension to colonial New Zealand.”…”
Section: [Aʊ] [εʊ] and The Settlersmentioning
confidence: 99%
“…The framework in this thesis is therefore informed by a cross-disciplinary body of literature exploring a myriad of trans-Tasman 'communities of interest', joint institutional arrangements and transnationalism. Sharing a reasonable level of consistency and coherence in beliefs and practices, together they represent a trans-Tasman 'way of doing things' (James 2009;Kirby 2002Kirby , 2010Lynch 2008;McCaskill 1982;Mein Smith 2011;Mein Smith et al 2008;O'Sullivan 2011;Simms 2006;Smith 2009;Tapp 1964). This body of literature, reviewed in Chapter Three, supports my case for a realm of enduring trans-Tasman political traditions which Australia, in making its 2001 decisions, chose to unilaterally change.…”
Section: Literature On Traditions Applied To Australia and New Zealandmentioning
confidence: 61%
“…Principally, extant studies explore how Australian and New Zealand settler societies began with shared sets of ideas about governance inherited, indeed transplanted, from British Westminster traditions which then evolved and developed over time with both similarities and differences in practices and interpretations (Rhodes 2005;Wanna 2005;Wanna and Weller 2003). Both countries were "innovators and experimenters politically and constitutionally" (Simms 2006: 688), with the sharing of policies and exchange of legislative practices a reality since responsible government was established from the mid-1880s (McCaskill 1982;Simms 2006). Literature exploring the foundational traditions of development, local expressions of Westminster traditions of responsible government and neoliberal reinterpretations are reviewed in Chapter Two, where traditions of exclusiveness/ inclusiveness are also identified through the policymaking that gives expression to them.…”
Section: Literature On Traditions Applied To Australia and New Zealandmentioning
confidence: 99%